Социология искусства: новые реалии, старые проблемы - Шульга, Р. (Социология: теория, методы, маркетинг, 1999)
The purpose of the sociology of art is to study the full spectrum of relations within aprocess of art’s functioning in society as also the full range of recipient’s real needsduring his/her communication with art. A constructive discussion of the subject of the sociology of art is connected with methodological renovation according to the newrealities, to give a new meaning of the herited paradigms and concepts related on ideology and mythology, which determine an understanding of culture in generaland artistic culture in particular. It is quite necessary to expose different levels of culture’s existence and functioning, to get clear understanding of differences between proper and real in explanation of culture phenomena; and adequate comprehension of real attitude to art, which is reflected in the Weltschauung consciousness of our compatriots.